An observational study on the relationship between serum uric acid and hypertension in a Northern Chinese population aged 45 to 59 years. Issue 17 (April 2017) - Yu, Feng-Na; Shi, Yun-Xia; Cheng, Hai-Ying; Huang, Xun-Lan; Liu, Shan-Shan
Abstract : Abstract: Little is known about the relationship serum uric acid (SUA) and hypertension in Chinese population. Therefore, the aim of this study was to determine the association between SUA and hypertension in a northern Chinese population. The participants were a group of 1730 Chinese adults aged 45 to 59 years in Shandong Province, who were recruited from the Linyi Nutrition and Health Survey (2015–2016). Hypertension was defined as systolic blood pressure ≥140 mm Hg and/or diastolic blood pressure ≥90 mm Hg. Hyperuricemia was defined as SUA >420 μmol/L (7.0 mg/dL) for men and >360 μmol/L (6.0 mg/dL) for women. All anthropometric measurements and biochemical data were collected following standard protocols. Multivariate logistic regression analysis was used to examine the association between SUA and hypertension with adjustment of confounding variables. Body mass index, waist circumference, waist-to-hip ratio, systolic blood pressure, diastolic blood pressure, fasting blood glucose, triglycerides, alanine aminotransferase, aspartate aminotransferase, SUA, and the prevalence of hypertension and hyperuricemia were significantly higher in males than in females ( P  < .001). The females had significantly higher levels of total cholesterol and high-density lipoprotein cholesterol. Besides, after adjustment for confounding variables, hyperuricemia was associated with an increased risk of hypertension in both male and female patients, with odds ratios of 2.152 (95% confidence interval 1.324–3.498) and 2.133(95% confidence interval 1.409–3.229), respectively. Hyperuricemia was significantly associated with the risk of hypertension. Further longitudinal studies and trails are needed to confirm our findings.